'Employment suitable for capabilities': The medical-legal principle in Italian invalidity social security benefits in the current historical work context in Europe. Issue 3 (September 2018) - Sammicheli, Michele; Scaglione, Marcella
The authors 1 trace the evolution of the social security concept of capability for work in 'employment suitable for skills'. This principle emerged at the end of the 1930s during the Fascist period, and it is the foundation for the current Italian law (no. 222 of 1984) relating to social security insured sickness. Having described the concept and its historical evolution, they highlight the developments that have had to take place in the last decade, due to changes in working conditions and the growing economic crisis that has affected all of Europe. They then analyse three cases to confirm that the recent economic crisis in the Italian and European labour markets has had an impact on the medical-legal assessment of a work activity as suitable for the capabilities. A careful examination of the relationship between sickness, disability and capacity for work in other EU and non-EU countries is undertaken to highlight the delicate social and medical issues surrounding job retention and the return of disabled persons to work.